2015
DOI: 10.1039/c5dt00269a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoheterogeneous catalysis in electrochemically induced olefin perfluoroalkylation

Abstract: Ni-catalyzed electroreductive olefin perfluoroalkylation affords both monomeric and dimeric products depending on the reaction media. Recycling of the catalyst can be achieved by immobilization of a (bpy)NiBr2 complex on silica nanoparticles decorated with anchoring amino-groups. Switching the homogeneous and heterogeneous catalysts is found to be one more factor to control the product ratio. This catalytic technique is both green and atom economical and combines the advantages of nanoheterogeneous catalysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The addition of a C6F13I substrate increases the current of the first reduction waves in the complex, suggesting that the Ni(I) species are the active forms of the catalyst. Due to the presence of two chiral carbon atoms in the dimerization products, three isomers were characterized by a variety of analytical techniques, including multi-dimensional NMR methods and X-ray single crystal diffraction [71,101]. The cyclic voltammetry study of the [Ni(tpy)Br 2 ] complex, along with fluoroalkyl halides, demonstrated that [Ni(I)(L)Br] is the active form of the catalyst.…”
Section: Electrochemical Nickel-induced Fluoroalkylation Of Olefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of a C6F13I substrate increases the current of the first reduction waves in the complex, suggesting that the Ni(I) species are the active forms of the catalyst. Due to the presence of two chiral carbon atoms in the dimerization products, three isomers were characterized by a variety of analytical techniques, including multi-dimensional NMR methods and X-ray single crystal diffraction [71,101]. The cyclic voltammetry study of the [Ni(tpy)Br 2 ] complex, along with fluoroalkyl halides, demonstrated that [Ni(I)(L)Br] is the active form of the catalyst.…”
Section: Electrochemical Nickel-induced Fluoroalkylation Of Olefinsmentioning
confidence: 99%
“…The electrocatalytic generation of a Ni(I) catalyst by reduction of a Ni(II)-tpy precursor complex in the presence of olefinic substrates and fluoroalkyl halides leads to new organic products derived from addition-dimerization processes (Scheme 19), showing a direct evidence of the importance of the four-coordinate low valent [Ni(tpy)Br] complex. Due to the presence of two chiral carbon atoms in the dimerization products, three isomers were characterized by a variety of analytical techniques, including multi-dimensional NMR methods and X-ray single crystal diffraction [71,101]. The cyclic voltammetry study of the [Ni(tpy)Br2] complex, along with fluoroalkyl halides, demonstrated that [Ni(I)(L)Br] is the active form of the catalyst.…”
Section: Electrochemical Nickel-induced Fluoroalkylation Of Olefinsmentioning
confidence: 99%
“…Thus, new electrochemical reactions of the C(sp 2 )-H phosphorylation [20][21][22][23][24][25][26][27] have been proposed in recent years. The progress of electroorganic synthesis in this field is described in numerous reviews 22,23,[28][29][30][31][32] and papers concerning some recent advances in C-H functionalization, such as fluoroalkylation, [33][34][35][36][37][38] amination, [39][40][41][42] aziridination, 43 oxygenation, [44][45][46] arylation, 47 alkylation, 48 amino-oxygenation, 49 etc. The first electrochemical oxidative phosphorylation of benzoxazoles in the presence of a 3d metal catalyst was reported in 2016.…”
mentioning
confidence: 99%
“…Controllable electrochemical behavior is a prerequisite for an application of the hybrid nanoparticles in electrochemical catalysis or sensing. In turn, nanoheterogeneous catalysts and sensors are of particular importance due to their greater stability and reusability versus the molecular complexes [14,15,17,18]. The substrate dependent electrochemical behavior of transition metal ions and complexes is the basis for electrochemical detection of many pollutants, including organophosphorous ones [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%